Constructal design of salt‐gradient solar pond fields. (5th April 2016) - González, Daniel; Amigo, José; Lorente, Sylvie; Bejan, Adrian; Suárez, Francisco
Summary: Salt‐gradient solar ponds (SGSPs) are water bodies that capture and accumulate large amounts of solar energy. The design of an SGSP field has never been analyzed in terms of studying the optimal number of solar ponds that must be built to maximize the useful energy that can be collected in the field, or the most convenient way to connect the ponds. In this paper, we use constructal design to find the optimal configuration of an SGSP field. A steady‐state thermal model was constructed to estimate the energy collected by each SGSP, and then a complementary model was developed to determine the final temperature of a defined mass flow rate of a fluid that will be heated by heat exchangers connected to the solar ponds. By applying constructal design, four configurations for the SGSP field, with different surface area distribution, were evaluated: series, parallel, mixed series‐parallel and tree‐shaped configurations. For the study site of this investigation, it was found that the optimal SGSP field consists of 30 solar ponds of increasing surface area connected in series. This SGSP field increases the final temperature of the fluid to be heated in 22.9%, compared to that obtained in a single SGSP. The results of this study show that is possible to use constructal theory to further optimize the heat transfer of an SGSP field. Experimental results of these configurations would be useful in future works to validate the methodology proposed in this study. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Using constructal design, it was found that, compared with a single salt‐gradient solar pond, an salt‐gradient solar pond field comprised by solar ponds connected in series with increasing area distribution increases significantly the energy that can be extracted from this thermal system.